Contralateral Noise Stimulation Delays P300 Latency in School-Aged Children - Ubiali, Thalita; Sanfins, Milaine Dominici; Borges, Leticia Reis; Colella-Santos, Maria Francisca (PLOS ONE, 2016)
Background and Objective The auditory cortex modulates auditory afferents through the olivocochlear system, which innervates the outer hair cells and the afferent neurons under the inner hair cells in the cochlea. Most of the studies that investigated the efferent activity in humans focused on evaluating the suppression of the otoacoustic emissions by stimulating the contralateral ear with noise, which assesses the activation of the medial olivocochlear bundle. The neurophysiology and the mechanisms involving efferent activity on higher regions of the auditory pathway, however, are still unknown. Also, the lack of studies investigating the effects of noise on human auditory cortex, especially in peadiatric population, points to the need for recording the late auditory potentials in noise conditions. Assessing the auditory efferents in schoolaged children is highly important due to some of its attributed functions such as selective attention and signal detection in noise, which are important abilities related to the development of language and academic skills. For this reason, the aim of the present study was to evaluate the effects of noise on P300 responses of children with normal hearing. Methods P300 was recorded in 27 children aged from 8 to 14 years with normal hearing in two conditions: with and whitout contralateral white noise stimulation. Results P300 latencies were significantly longer at the presence of contralateral noise. No significant changes were observed for the amplitude values. Conclusion Contralateral white noise stimulation delayed P300 latency in a group of school-aged children with normal hearing. These results suggest a possible influence of the medial olivocochlear activation on P300 responses under noise condition.